Developing Skills for Youthful Leaders Module 5: Listening Skills to Improve Communication - Elizabeth B. Bolton; John R. Rutledge; Linda Bowman; Linda Barber (EDIS, 2006)
The objectives of this lesson are to learn that listening is part of communication, to learn how to listen, to overcome barriers to good listening, to understand feedback as a communication tool, and to learn how to provide feedback as a test of listening. This document is FCS9092, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. EDIS publication date May 2006.